Kenneth Slessor - Semmler, Clement (Writers and Their Work Series., 1966)
Kenneth Slessor, born Igor, is by general consent among the foremost of Australian poets and, by the acclaim of some, the best. Australia's most distinguished literary historian, H.M. Green, wrote of his poetic technique that it was not only superior to that of any other Australian poet of his generation but comparable at its best with that of any contemporary in England or the United States Mr Semmler who writes in appreciation of Slessor is the Deputy Ge.